Fast, sensitive and specific diagnosis of infections with Leishmania spp. in formalin‐fixed, paraffin‐embedded skin biopsies by cytochrome b polymerase chain reaction. (23rd October 2015) - Gebhardt, M.; Ertas, B.; Falk, T.M.; Blödorn‐Schlicht, N.; Metze, D.; Böer‐Auer, A.
Summary: Background: Northern spread of sandflies and Leishmania spp. has been observed in Europe. Diagnosis can be difficult owing to the various clinical manifestations. Species identification is important for patient management and therapy. Molecular diagnostics is increasingly used for pan‐ Leishmania detection but species identification remains challenging in formalin‐fixed material. Objectives: To apply cytochrome b (cytb) polymerase chain reaction (PCR) and sequencing for identification of Leishmania species on formalin‐fixed, paraffin‐embedded (FFPE) skin biopsies; and to identify species‐specific histological patterns. Methods: Sixty‐nine biopsies (48 patients) diagnosed with leishmaniasis based on the presence of amastigotes in the tissue ( n  =   41) or granulomatous infiltrates with positive pan‐Leishmania real‐time PCR ( n  =   28) were analysed with cytb PCR, sequencing and phylogenetic analysis. Histological sections were analysed; epidemiological data were collected. Results: Cytb PCR identified Leishmania in all specimens: L. infantum (79%), L. major (8%), L. panamensis (4%), L. tropica (4%), L. killicki (2%) and L. aethiopica (2%). Of the detected species 95% were endemic to the country in which the infection was acquired. Amastigotes were found in 59%. Infiltrates were mainly tuberculoid granulomatous (65%), interstitial (15%) and sarcoidal (10%). Pseudolymphomatous features and pseudocarcinomatous hyperplasia were more common in L. major infections than in L. infantum ( P  <   0·01). Conclusions: Cytb PCR and sequencing is a fast, reliable and sensitive assay for identification of Leishmania spp. in FFPE biopsies. Leishmania infantum is the main cause of cutaneous leishmaniasis in Germany. Tuberculoid granulomas, other types of granulomas and pseudolymphomatous infiltrates may be encountered; the latter being indicative of infection with L. major . Abstract : What's already known about this topic? Owing to tourism and the spread of sandflies, leishmaniasis is increasing in northern Europe. Clinical appearance is variable. Molecular diagnostics are used for pan‐ Leishmania detection, but species identification remains challenging, especially in formalin‐fixed, paraffin‐embedded (FFPE) material. Species identification is important for patient management/therapy. What does this study add? Cytochrome b polymerase chain reaction is a fast, reliable and sensitive assay for the identification of human pathogenic Leishmania spp. in FFPE biopsies. Pseudolymphomatous infiltrates and pseudocarcinomatous hyperplasia often indicate infection with Leishmania major .